Biscembranoids from Vietnamese marine sponge Petrosia nigricans - Quang, Ngo Van; Nhiem, Nguyen Xuan; Thuy Hang, Dan Thi; Tuan Anh, Hoang Le; Yen, Pham Hai; Dung, Duong Thi; Cuc, Nguyen Thi; Minh, Chau Van; Mai Phuong, Nguyen Thi; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
Three biscembranoids, lobophytone H (1), lobophytone U (2), and methyl tortuoate B (3), were isolated from the methanol extract of Vietnamese marine sponge Petrosia nigricans. Their structures were determinated on the basis of 1D and 2D-NMR, HR-ESI-MS and in comparison with the reported data.